Peranan guru kelas sebagai pembimbing pada siswa SD - Nurhasanah Nurhasanah; Jamilah Aini Nasution; Zahra Nelissa; Fitriani Fitriani (Jurnal Suloh, 2021)
One of the roles of the homeroom teacher is as a guide. At elementary school, the teacher has complex responsibilities in addition to teaching as well as guiding students so that they can achieve developmental tasks optimally. This research destination is to know the role of homeroom teacher as a guide for elementary students in Banda Aceh by using a quantitative descriptive approach. The subject of the research total was 101 homeroom teachers in 9 elementary schools Banda Aceh. The data collection tool used was a questionnaire. The results of the descriptive data analysis show that the role of homeroom teacher as a guide in elementary schools Banda Aceh is were 95 homeroom teachers on very high category (94%), in the high category 5 homeroom teacher (5%), then in the moderate category 1 homeroom teacher (1%). The condusion that the homeroom teachers in elementry school at Banda Aceh have been as a guide on students which doing guidance there are (1) identification the needed of students, (2) the formulate of destinations in study and steer students about the destinations of study, (3) ) giving the notice to students in according with the needed and the trouble and responsible in their life, (4) giving briefing or orientation which efective in study, (5) guide relationship beetwen individu and their social, (6) make a students as an individu how have self esteem, opennes, responsible and freedom, (7) cooperate with counselors and the other teachers in giving aid which the students needed. The implication of this research is that homeroom teachers can upgrade their performance as a guide to students in elementary school at banda aceh, so the students can grow and developing in optimal.   Keywords: Roles; Homeroom Teacher; Guide; Elementary School Student ABSTRAK Salah satu peranan Guru Kelas adalah sebagai pembimbing. Pada tingkat SD Guru memiliki tanggung jawab kompleks selain mengajar juga membimbing agar siswa dapat mencapai tugas-tugas perkembangan secara optimal. Penelitian ini bertujuan untuk mengetahui peranan Guru Kelas sebagai pembimbing pada siswa SD Kota Banda Aceh dengan menggunakan pendekatan deskriptif kuantitatif. Subjek penelitian berjumlah 101 orang Guru Kelas dari 9 SD di Kota Banda Aceh. Alat pengumpulan data yang digunakan berupa Angket. Hasil analisis deskriptif data menunjukkan bahwa Guru Kelas yang berperan sebagai pembimbing di SD Kota Banda Aceh ialah 95 orang Guru Kelas berada pada kategori sangat tinggi (94%), pada kategori tinggi 5 orang Guru Kelas (5%), kemudian pada kategori sedang 1 orang Guru Kelas (1%). Dapat disimpulkan bahwa Guru Kelas di SD Kota Banda Aceh sudah bertanggung jawab penuh dalam menjalankan perannya sebagai pembimbing pada siswa dengan melakukan kegiatan bimbingan yaitu: (1) mengidentifikasi kebutuhan peserta didik, (2) merumuskan tujuan pembelajaran dan mengarahkan siswa sesuai tujuan pembelajaran, (3) memberikan nasihat kepada siswa sesuai kebutuhan dan kesulitan yang dialaminya serta bertangung jawab dalam kehidupan, (4) memberikan pengarahan atau orientasi dalam rangka belajar yang efektif, (5) membina hubungan yang baik antar pribadi dan sosialnya, (6) memperlakukan siswa sebagai individu yang mempunyai harga diri, keterbukaan, tanggap dan kebebasan, (7) bekerja sama dengan konselor dan tenaga pendidik lainnya dalam memberikan bantuan yang dibutuhkan siswa. Implikasi penelitian ini Guru Kelas senantiasa dapat meningkatkan kinerja sebagai pembimbing pada siswa SD Kota Banda Aceh, sehingga siswa dapat tumbuh dan berkembang secara optimal.